An evaluation of macrosomia risk factors in a cohort of Chinese women and neonates - Rui Xue; Zhongming Yun (Journal of International Medical Research)
Objective We aimed to identify risk factors for macrosomia in women with high-risk pregnancies, which will allow for early identification and timely intervention and improve the health of mothers and infants. Methods A retrospective case–control study was conducted of pregnant women and neonates born at Shenmu Hospital in China between 1 January 2020 and 31 December 2023. Cases comprised neonates with macrosomia (birth weight ≥4000 g), and controls comprised a group of normal-weight neonates (birth weight 2500–3999 g). Conditional logistic regression analysis was performed to identify independent predictor variables. Results In total, 10,253 cases with complete maternal and neonatal-related data were included in this study, with 1100 cases in the macrosomia group and 9153 in the control group. Male neonates (odds ratio = 1.636), gestational age (odds ratio = 1.726), maternal height ≥165 cm (odds ratio = 3.648), prepregnancy body mass index ≥28 kg/m 2 (odds ratio = 2.733), excessive weight gain during pregnancy (odds ratio = 2.817), ≥2 pregnancies (odds ratio = 1.368), ≥2 prior deliveries (odds ratio = 1.285), gestational diabetes (odds ratio = 3.227), excess amniotic fluid (odds ratio = 4.592), scarred uterus (odds ratio = 0.693), gestational hypertension (odds ratio = 0.750), oligohydramnios (odds ratio = 0.262), and umbilical cord anomalies (odds ratio = 0.727) were all associated with an increased risk of macrosomia. Conclusions Women with high-risk pregnancies who have a height of ≥165 cm, ≥2 previous deliveries, prepregnancy obesity, and a scarred uterus should be provided with individualized prenatal care and delivery plans; for these women, monitoring weight gain, blood glucose, and amniotic fluid should be intensified along with targeted interventions to provide optimal care for this high-risk population.